Adoption of the International Financial Reporting Standard (9) for financial instruments and its impact on measurement and disclosure in financial investment companies (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:               The accounting measurement and disclosure requirements for financial instruments in the Iraqi environment differ from international financial reporting standards, and the adoption of international financial reporting standards leads to the possibility of comparison between companies’ financial statements in a way that serves many parties, including investors, in making their investment decisions. The research problem revolves around the lack of an application mechanism that is followed. By Al-Zawraa Financial Investment Company to adopt International Financial Reporting Standard No. (9) despite the Central Bank of Iraq issuing Circulars No. (9/12) on 1/4/2016 and (6/9) on 12/28/2018 to switch from The unified accounting system for banks and insurance companies is based on international accounting standards for financial reporting. The research aims to propose the necessary mechanism for applying the international financial reporting standard No. (9) for financial instruments and its reflection on the financial statements. The research reached a set of conclusions, the most important of which is not including the unified accounting system for banks and companies. Insurance has special accounting treatments for financial instruments. The adoption of international financial reporting standards contributes to showing the values of investments in the financial statements in a more fair manner. The adoption of Standard No. 9 will reflect more on the recorded values of investments, as the investment in the research sample before application amounted to (1,036,489,746) Iraqi dinars. While when applying the requirements for measuring financial investments according to standard (9), the amount became (406,107,113) Iraqi dinars